Effectiveness of Project-Based Learning Model Implementation with Peer Tutor Method in terms of Students' Active and Learning Outcomes in Graphic Design Subjects - Arinto Aji Suharto; Agus Efendi; Dwi Maryono (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2019)
This study aims to find out how the influence caused by the use of learning models on the activeness and learning outcomes. The method used in this research is quantitative quasi experimental design. The population in this study were 66 students of class X RPL A and B in SMK Negeri 5 Surakarta. The sampling technique in this study uses the cluster random sampling method and the number of samples refers to the total population of class groups. Data collection techniques are used in the form of questionnaires and tests. Hypothesis testing is done by t test and normalized gain test. The results used in this study are based on the significance value (sig.) Which has the meaning as a determinant of whether the hypothesis test results are accepted or rejected . So that the results of this study can be used as information for educators to be considered in preparing the learning process better. In addition, it encourages students to play an active role in learning so as to achieve the desired learning goals.Keywords: Learning Model, Project Based Learning, Peer TutorsThis study aims to find out how the influence caused by the use of learning models on the activeness and learning outcomes. The method used in this research is quantitative quasi experimental design. The population in this study were 66 students of class X RPL A and B in SMK Negeri 5 Surakarta. The sampling technique in this study uses the cluster random sampling method and the number of samples refers to the total population of class groups. Data collection techniques are used in the form of questionnaires and tests. Hypothesis testing is done by t test and normalized gain test. The results used in this study are based on the significance value (sig.) Which has the meaning as a determinant of whether the hypothesis test results are accepted or rejected . So that the results of this study can be used as information for educators to be considered in preparing the learning process better. In addition, it encourages students to play an active role in learning so as to achieve the desired learning goals.Keywords: Learning Model, Project Based Learning, Peer Tutors.